Enhancement of biogas production from sewage sludge in a wastewater treatment plant: Evaluation of pretreatment techniques and co-digestion under mesophilic and thermophilic conditions. (15th August 2018) - Mirmasoumi, Siamak; Ebrahimi, Sirous; Saray, Rahim Khoshbakhti
Abstract: Boosting biomethane production makes it possible to offset the required energy in a wastewater treatment plant. In this research, using batch biomethane potential assays, various techniques including pretreatment, co-digestion, and digestion temperature rise were evaluated to increase the methane productivity of municipal sewage sludge (SS). Between thermal and sonication pretreatment methods, thermal pretreatment was shown to be more efficient and there was no need to pretreat SS for more than 0.5 h. Thermophilic digestion of SS led to 160.8% rise in the methane productivity, compared to mesophilic digestion. The most suitable co-substrate for co-digestion with SS was food waste (FW). FW and SS had little negative synergistic effect, however higher FW concentration caused to higher specific methane yield. Thermal pretreatment was not effective on FW. To evaluate the techniques, a combined cooling, heat and power plant was suggested. The energy recovery balance was positive for all the techniques, but co-digestion was not successful to reduce the levelized cost of energy (LCOE). Unlike co-digestion, thermal pretreatment and digestion temperature rise decreased the LCOE. The thermophilic digestion of SS, pretreated at 90 °C for 0.5 h, resulted in the lowest amount of LCOE by 43.70% reduction, compared to the mesophilic single digestion of non-treated SS. Highlights: Evaluation of various techniques to increase biogas productivity of sewage sludge. For the same energy applied, thermal pretreatment was more effective than sonication. Digestion temperature rise led to significant increase in the methane productivity. Co-digestion with food waste could not reduce the levelized cost of energy (LCOE). Thermal pretreatment before thermophilic digestion significantly decreased the LCOE.